Information-Library-Knowledge - Kundačina, Bojan; Jovičić, Stanka (Qualitative and Quantitative Methods in Libraries, 2019)
Library of Alexandria was the most modern library in the ancient times. However the abundance of books could not acquire a considerable significance, commensurate with its true merits, since the books were not systematically arranged, as a result of which finding the right information was too time consuming. Realizing a problem, Kalimah initiated the process of systematization and finding appropriate location for each type of written literature material. Nowadays we are facing an important question: can we confer Kalimah's role on the Internet or web browsers, or is that role exactly the one which the library cannot afford to lose in the 21st century? Trying to respond to this dilemma, Belgrade City Library has launched the portal „Šta da čitam?“(What shall I read?), in cooperation with the majority of public libraries in Serbia. The goal of the portal, designed in the new era and with new tools, is to asume the role libraries have always had – namely, to bring quality books/knowledge closer to their users/readers. However, this task is becoming increasingly difficult for both readers and libraries, as literary production is seeing a marked and constant rise. Information and knowledge are two distinctly separate terms; the future role of the library should not only be to select items of information and extract only the relevant ones from the ocean of data, but also to perform an adequate analysis based on the information available. The latest research has shown that, despite an enormous inflow and ever-greater accessibility of data over the past 50 years, the citizens are not better informed then before. In fact, more information leads to more confusion and knowledge fragmentation. Inundated with more and more information, we are facing a real threat of becoming overwhelmed with trivia, unable to reach important and essential information.